Benign External Hydrocephalus in Infants: A Single Centre Experience and Literature Review. Issue 2 (April 2014) - Marino, Maria Adele; Morabito, Rosa; Vinci, Sergio; Germanò, Antonino; Briguglio, Marilena; Alafaci, Concetta; Mormina, Enricomaria; Longo, Marcello; Granata, Francesca
External hydrocephalus (EH) is a benign clinical entity in which macrocephaly is associated with an increase in volume of the subarachnoid space, especially overlying both frontal lobes, and a normal or only slight increase in volume of the lateral ventricles. Several pathogenic hypotheses have been proposed but the most accredited theory seems to be delayed maturation of the arachnoid villi. There is a consensus that this is a benign entity, correlated to a familial predisposition and, in some cases, inheritance. CT and MRI are very important to make a diagnosis but also to establish the prognosis in patients who encounter the rare complications such as subdural haematomas. In conclusion, CT and MRI can provide a highly accurate diagnosis in these patients, allowing a preliminary assessment of the prognosis, particularly regarding the enlarged subarachnoid space limits and the "cortical vein" sign which can predict a further complication. These results are obtained with the same examination performed in a standard CT or MRI study of the brain and no injection of contrast medium is needed.